2022
DOI: 10.1021/acsnano.2c07813
|View full text |Cite
|
Sign up to set email alerts
|

An Ionic Diode Covalent Organic Framework Membrane for Efficient Osmotic Energy Conversion

Abstract: Heterogeneous membranes that exhibit an ionic diode effect are promising candidates for osmotic energy conversion. However, existing heterogeneous membranes lack molecular-level designed ion channels, thereby limiting their power densities. Here, we demonstrate ionic diode covalent organic framework (COF) membranes with well-defined ion channels, asymmetric geometry and surface charge polarity as high-performance osmotic power generators. The COF diode membranes are comprised of heterojunctions combining a pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 64 publications
1
29
0
Order By: Relevance
“…In a recent study, two oppositely charged COFs (TpPa-SO3Na and TpEB) with hundreds of nanometers were used to form an ionic diode and a rectification ratio ≈13 was achieved. [31] Finally, we should note that the COFs are considered to be treated as rigid. Despite the fact that such a treatment is commonly utilized in simulation studies, [28,29] framework flexibility is not taken into account.…”
Section: Different Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent study, two oppositely charged COFs (TpPa-SO3Na and TpEB) with hundreds of nanometers were used to form an ionic diode and a rectification ratio ≈13 was achieved. [31] Finally, we should note that the COFs are considered to be treated as rigid. Despite the fact that such a treatment is commonly utilized in simulation studies, [28,29] framework flexibility is not taken into account.…”
Section: Different Conditionsmentioning
confidence: 99%
“…[ 30 ] After the submission of the current study, an ionic diode COF membrane was reported by comprising two oppositely charged COFs (TpPa‐SO 3 Na and TpEB) and demonstrated efficient osmotic energy conversion. [ 31 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data are for C2DPs, 7 PyPa-SO 3 H/SANF, 28 bulk COF, 16 BDA-TAM, 58 monolayer COF, 59 and TpEB@TpPa-SO 3 Na. 60 Journal of the American Chemical Society selectivity coefficient decreases with the increase of the salinity gradient, which is mainly caused by the decrease of the Debye length with the increase of salt solution concentration. Encouraged by the high conductance, fast ion transport channels, and extremely stable frame structure of the resultant sp 2 c-COF films, the TFPT−TMT was selected to further fabricate an osmotic power generator in varied working environments at pH = 7, pH = 10, and pH = 14 with 50-fold NaCl salinity gradient.…”
Section: ■ Introductionmentioning
confidence: 99%
“…(f) The permeable power generation performance of the TFPT−TMT membrane is compared with that of the imine-linked COF membrane reported recently. Data are for C2DPs,7 PyPa-SO 3 H/SANF,28 bulk COF,16 BDA-TAM,58 monolayer COF,59 and TpEB@TpPa-SO 3 Na 60.…”
mentioning
confidence: 99%